Educação à distância no Brasil: o impacto da evasão do ensino - Ferreira, Diogo Gonçalves (2024)
This study is linked to the State, Policies and Educational Institutions Research Line of the Postgraduate Program in Education at the Pontifical Catholic University of Goiás (PPGE/GOIÁS). Entitled Distance Education in Brazil: A study of dropout rates in distance education in Brazil, it looks at the impacts of the growth of distance education in the country from 2012 to 2022. It aims to carry out a contextualized research of the material collected through a bibliographic and documentary review, which aims to reflect, from a dialectical materialist perspective, on distance education and dropout, since it is necessary to look for causes and propose solutions. Considering the multiple determinations of neoliberalism and mercantilism seen today in education, more especially in Distance Education, this thesis relates the technicist, human coefficient to data from Mec/Inep (from 2012 to 2022), analyzing the profile of students who drop out, seeking to understand their models and find strategies to contain it, since since 2021, the number of entrants to remote courses has grown exponentially. This research also points out that neoliberalism, an economic model based on free competition, increases the exploitation, weakening and devaluation of workers/tutors in education. This study also highlights the importance of the active participation, resistance and mobilization of workers in opposition to the setbacks in education against the excesses of the School without a Party. The study concludes that the future of distance education lies in the continued training of the educational agents involved in the process, in the creation of strategies to retain students in order to involve them more and more with affection and a sense of belonging, as well as in the adoption of new technological tools such as AI (Artificial Intelligence)